"Feeling Less Than a Second Class Citizen": Examining the Emotional Consequences of Poverty in New York City. (July 2018) - Ali, Samira; Sensoy Bahar, Ozge; Gopalan, Priya; Lukasiewicz, Karolina; Parker, Gary; McKay, Mary; Walker, Robert
It has been argued that individuals living in poverty are shamed, and thus, experience it in various social and institutional spaces. However, little is known about this dynamic in the United States. This study examined the relationship between poverty and shame among individuals living in poverty. Individual semistructured interviews were conducted with 60 participants in New York, NY. The results reveal that participants experience shame, anger, and frustration in their roles as (a) caregivers when being unable to provide material items and trying to keep up with others in society and (b) social welfare recipients when at the welfare office and accessing welfare benefits. Despite experiencing such debilitating emotions, participants formulated and used strategies to manage these feelings and situations. These findings point to the role of social and institutional practices in shaping emotions.